Peranan Mediator Ketenagakerjaan Dalam Penyelesaian Perselisihan Hubungan Industrial Di Dinas Ketenagakerjaan Kota Tangerang Berdasarkan Undang Undang Nomor 2 Tahun 2004: Kasus Penyelesaian Perselisihan Hubungan Industrial Di PT.Kreasi San Ginesio dan PT. Matahari Plastindo - Rudianto Silalahi (to-ra, 2020)
Problems of industrial relations from time to time, basically arises due to changes in values ​​and internal and external factors. Seeing the large number of industrial disputes arising between companies and workers, it is needed a mediator to bridge these disputes. Termination of employment can not be done at will of the employer, but must be done with a strong reason and grounds, as regulated in Article 158 of Law Number 13 of 2003 concerning Manpower. The research conducted is a descriptive analysis, which describes or illustrates the overall problem in the study associated with the provisions in the literature, legislation, and then analyzed the problems that have to do with the object of the problem. The first discussion about the factors that cause industrial relations disputes between workers and employers is due to violations of the law in general due to differences in understanding in the implementation of labor law, this is reflected in the actions of employers who violate legal provisions. Disputing parties must negotiate the Bipartite at the company level through deliberation; make complaints and record industrial relations disputes to the Social Service, Labor and Transmigration Tangerang if there is a failure in the Bipartite negotiations that have been carried out by bringing letters or documents that can support these complaints, especially the minutes of the Bipartite negotiations, the establishment of mediation as a path for resolving industrial relations disputes. Keywords: Labor, Industrial Relations Disputes, Mediation